Pengembangan Media Pembelajaran Audiovisual untuk Meningkatkan Hasil Belajar Siswa : Penelitian - Ifan Jerita Harefa; Arozatulo Bawamenewi; Riana; Imansudi Zega (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Audiovisual learning media is very important for students because it can help them understand the subject matter more easily and enjoyably. The purpose of this study is to develop Audiovisual learning media to improve student learning outcomes in the material reviewing fictional works about the Malin Kundang fairy tale and to find out the feasibility of content, feasibility of presentation, and feasibility of developing Audiovisual learning media with the Addie model. The subjects of the study were 21 students of class VIII-A of SMP Negeri 1 Namohalu Esiwa in the even semester. This type of research is development or called Research and Development (R&D) and data collection techniques are Media Practicality Questionnaires and Essay Tests. Product trial activities were carried out twice, small group trials of 6 students and large group trials of 15 students. Based on the results of the study, it can be seen from the material validation reaching 100%, language validation reaching 72% and design validation reaching 86%. Media practicality trials reaching 82.42% and media effectiveness trials reaching 74.81%. It is concluded that the development of Audiovisual learning media to improve student learning outcomes in class VIII-A of SMP Negeri 1 Namohalu esiwa is very well developed. It is hoped that further researchers will use this research as additional insight to conduct research.